Tax shields, financial expenses and losses carried forward (2016)
This article deals with the proper procedure for calculating Tax Shields (TS). The calculation includes cases where Losses Carried Forward are allowed and there is financial Other Income (OI). The procedure takes into account the magnitude of Adjusted Earnings before Interest and Taxes (EBITAdj) –that is, EBIT + OI – OE excluding Financial- compared with Financial Expenses (FE). This comparison defines three intervals and results for TS. If EBITAdj. 0, TS will be 0; if EBITAdj. 0 and less than FE, TSis T × EBITAdj.; finally if EBITAdj. FE, TSis T × FE. When firm possesses OI, TS are not equivalent to the difference in taxes and an adjustment is needed. Proper calculation of TS is important because their value might represent a substantial part of firm value.